Comparison of the Techno-Economic and Environmental Assessment of Hydrodynamic Cavitation and Mechanical Stirring Reactors for the Production of Sustainable Hevea brasiliensis Ethyl Ester - Samuel O.D.; Aigba P.A.; Tran T.K.; Fayaz H.; Pastore C.; Der O.; Eretin A.; Enweremadu C.C.; Mustafa A. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Even though the hydrodynamic cavitation reactor (HCR) performs better than the mechanical stirring reactor (MSR) at producing biodiesel, and the ethylic process of biodiesel production is entirely bio-based and environmentally friendly, non-homogeneous ethanol with the triglyceride of underutilized oil, despite the many technical advantages, has discouraged the biodiesel industry and stakeholders from producing ethylic biodiesel in HCRs. This study examines the generation of biodiesel from rubber seed oil (RSO) by comparing the ethyl-based HCR and MSR. Despite ethyls technical advantages and environmental friendliness, a lack of scalable protocols for various feedstocks hinders its global adoption. The research employs Aspen HYSYS simulations to investigate the ethanolysis process for RSO in both HCRs and MSRs. The HCR proves more productive, converting 99.01% of RSO compared to the MSRs 94.85%. The HCRs exergetic efficiency is 89.56% vs. the MSRs 54.92%, with significantly lower energy usage. Removing catalytic and glycerin purification stages impacts both processes, with HC showing lower exergy destruction. Economic analysis reveals the HCRs lower investment cost and higher net present value (USD 57.2 million) and return on investment (176%) compared to the MSRs. The HCR also has a much smaller carbon footprint, emitting 7.2 t CO2 eq./year, while the MSR emits 172 t CO2 eq./year. This study provides database information for quickly scaling up the production of ethanolic biodiesel from non-edible and third-generation feedstocks in the HCR and MSR. 2023 by the authors.